ДИСТАНЦІЙНЕ НАВЧАННЯ МАЙБУТНІХ МАГІСТРІВ ФАРМАЦІЇ: ПРОБЛЕМИ ТА ШЛЯХИ ЇХ РОЗВ’ЯЗАННЯ - Людмила Миколаївна Клос (International Journal of Innovative Technologies in Social Science, 2019)
The article deals with the issues of organizing the preparation of future masters of pharmacy in the conditions of society’s informatization. An analytical review of the specifics of the professional training of specialists in the pharmaceutical industry is carried out. The problems caused by the need for pharmacists to effectively treat and prevent viral diseases are outlined. The author has proved that the profession of pharmacist in its essence is a process of constant development, self-development and improvement and self-improvement, where raising the level of knowledge and the formation of practical skills form the basis of its activities. Considering that the pharmaceutical industry is undergoing significant changes and requires continuous scientific and educational support. It is concluded that a modern pharmacist should be able to increase his personal professional qualification at a convenient time for him, remotely, including both online and offline.